TANTANGAN GURU BK DALAM MEMBERIKAN PENDAMPINGAN KEPADA SISWA YANG MENGALAMI MASALAH KELUARGA - Burma, Ulyatus Sufi; Desmi, Desmi; Nurhayani, Nurhayani; Hayuki, Mitra (Jurnal Manajemen Pendidikan, 2026)
Family problems are all forms of behavior, actions, dynamics, patterns and interactions That disturbs the family, whether from any side. As part of the support system in School, counseling guidance teacher (BK) has a great responsibility in giving Assistance for students who face family problems. This research aims to Analyze the role of counseling guidance teachers (BK) in providing assistance to Students at SMA Negeri 2 Bangko who face family problems, and identify Obstacles faced in the implementation of the task. Family problems, such as divorce Or economic problems, can have a significant impact on emotional, social development, and Academic student. The method used is an approach with a qualitative case study design.v By involving BK Teacher at SMA Negeri 2 Bangko as an informant, this research Using a semi-structured interview with reference to a list of open questions. This data analysis technique uses descriptive analysis that combines data from collections Said individual. Research results show that BK teachers have an important role in Accompany students through individual counseling services, parent education, and reinforcement Students' social skills. However, BK teachers face various obstacles, such as Limited time, lack of family support, stigma against BK services, and lack of Adequate resources.